NILAI BUDAYA BATIK TRUSMI DALAM PERKEMBANGAN ZAMAN: MODERNISASI, KONFLIK SOSIAL, DAN PELESTARIAN BUDAYA - Herawan, Vania Awaliyah; Agnia Ramadhani , Salma; Ghina Fawziya Nurherriza, Rizqita; Aurelia, Sherri; Tresna Wiyanti, Dede (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to understand the presence of Trusmi Batik as intangible cultural heritage from Cirebon and to analyze the values inherent in Trusmi Batik as times change. The focus of the research is on how Trusmi Batik perseveres in the era of technological advancement while maintaining its cultural values, as well as on analyzing the negative impacts and social conflicts that emerge. This research was conducted using a descriptive qualitative method with a case study approach. The results show that although various innovations have emerged in both motifs and techniques, the core motif of Trusmi Batik and the technique of writing batik using a canting remain relevant, accessible, and highly valued. Despite experiencing negative effects from modernization felt by the people of Trusmi Village, many preservation efforts are actively underway, which means Trusmi Batik continues to thrive today and will remain sustainable for the future. The concept applied in this study is inculturation, which is the integration of modern values into local culture to ensure the preservation of batik amid modernization.